Developing and user testing new pharmacy label formats-A study to inform labelling standards - Vivien Tong; Parisa Aslani; David K. Raynor; Diana Shipp; Brian Parkinson; Daniel Lalor; Andrew Sobey; Alice Gilbert; Jackie Crofton; Joanne Young; Sophie Carter; Wing Poon; et al. (Wiley, 2021)
Abstract Background Dispensed prescription medicine labels (prescription labels) are important information sources supporting safe and appropriate medicines use. Objective To develop and user test patient‐centred prescription label formats. Methods Five stages: developing 12 labels for four fictitious medicines of varying dosage forms; diagnostic user testing of labels (Round 1) with 40 consumers (each testing three labels); iterative label revision, and development of Round 2 labels (n = 7); user testing of labels (Round 2) with 20 consumers (each testing four labels); labelling recommendations. Evaluated labels stated the active ingredient and brand name, using various design features (eg upper case and bold). Dosing was expressed differently across labels: frequency of doses/day, approximate times of day (eg morning), explicit times (eg 7 to 9 AM), and/or explicit dosing interval. Participants' ability to find and understand medicines information and plan a dosing schedule were assessed. Results Participants demonstrated satisfactory ability to find and understand the dosage for all label formats. Excluding active ingredient and dosing schedule, 14/19 labels (8/12 in Round 1; 6/7 in Round 2) met industry standard on performance. Participants' ability to correctly identify the active ingredient varied, with clear medicine name sign‐posting enabling all participants evaluating these labels to find and understand the active ingredient. When planning a dosing schedule, doses were correctly spaced if the label stated a dosing interval, or frequency of doses/day. Two‐thirds planned appropriate dosing schedules using a dosing table. Conclusions Effective prescription label formatting and sign‐posting of active ingredient improved communication of information on labels, potentially supporting safe medicines use. Patient and Public Involvement Consumers actively contributed to the development of dispensed prescription medicine labels. Feedback from consumers following the first round was incorporated in revisions of the labels for the next round. Patient and public involvement in this study was critical to the development of readable and understandable dispensed prescription medicine labels.